SEDENTARY BEHAVIOR AND JUNK FOOD CONSUMPTION AMONG WORKING AGE ADULTS WITH HYPERTENSION - Adevia Maulidya Chikmah; Putri Widiyati; Muhammad Ibnu Hasan (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Hypertension is one of the most prevalent non-communicable diseases worldwide, with an increasing burden among working-age adults. Sedentary behavior and dietary patterns, including food consumption based on the NOVA classification, are considered important lifestyle factors that may contribute to hypertension. This study aimed to describe respondent characteristics, sedentary behavior, dietary patterns based on the NOVA food classification, and the distribution of hypertension among working-age adults. A quantitative descriptive study with a cross-sectional design was conducted among 37 working-age adults with hypertension recruited using accidental sampling. Data were collected using the Adolescent Sedentary Activity Questionnaire (ASAQ), a NOVA-based food frequency questionnaire, and blood pressure measurements. Data were analyzed descriptively using frequency distributions and percentages. Most respondents were late-middle-aged adults, female, housewives, and non-smokers. Grade I hypertension was observed in 51.3% of respondents, while 48.6% had Grade II hypertension. Moderate sedentary behavior was the most common category. Based on the NOVA classification, respondents frequently consumed foods from NOVA Group 1 and NOVA Group 2, whereas foods from NOVA Group 3 and NOVA Group 4 were consumed less frequently. The findings suggest that hypertension among working-age adults is a multifactorial condition influenced by multiple risk factors. Hypertension prevention strategies should therefore promote healthy lifestyle behaviors through increased physical activity, reduced sedentary behavior, healthier dietary practices, and regular blood pressure monitoring.